Fluorescence-based active site probes for profiling deubiquitinating enzymes. - McGouran, J; Kramer, H; Mackeen, M; di Gleria, K; Altun, M; Kessler, B (2012)
Novel ubiquitin-based active site probes including a fluorescent tag have been developed and evaluated. A new, functionalizable electrophilic trap is utilized allowing for late stage diversification of the probe. Attachment of fluorescent dyes allowed direct detection of endogenous deubiquitinating enzyme (DUB) activities in cell extracts by in-gel fluorescence imaging.